COASTAL VULNERABILITY PREDICTION TO CLIMATE CHANGE: STUDY CASE IN CIREBON COASTAL LAND - Ricky Rositasari; Wahyu B. Setiawan; Indarto H. Supriadi; Hasanuddin Hasanuddin; Bayu Prayuda (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2011)
Coastal area is the most vulnerable area to climate change. Cirebon coastal land in Western Java, Indonesia is low-lying coastal area which is one of the potential areal for fish culture and farming. There are also major transportation facilities for western Java province to the whole area in the island (Java) through this area. As low-lying landscape, populated and developing city, Cirebon should be considered vulnerable to future sea level rise. Geomorphology, geo-electric and remote sensing study were conducted during 2008 and 2009 in coastal land of Cirebon. The result showed that most part of coastal area in Cirebon was eroded in various scales which vulnerable turn to worst. Sea water was penetrating throughout several kilometres inland. Valuation on various land-uses would project 1,295,071,755,150 rupiah/ha/year of loss while sea level were rose 0.8 meters that would inundate various land-uses i.e., Shrimp, fish and salt ponds, rice fields and settlement in the area.Keywords: vulnerability, coastal, climate change, sea level rise